EVALUATION OF RELIABILITY OF RADIO-ELECTRONIC DEVICES WITH VARIABLE STRUCTURE - Ryzhov, Ye. V.; Sakovich, L. N.; Puchkov, O. O.; Nebesna, Ya. E. (Radio Electronics, Computer Science, Control, 2020)
Context. Various radio electronic devices are being continuously developed and refined in order to improve the quality indicators according to the consumers’ requirements for their use in multiple operational modes, each with separate subsets of elements. Given fact is not taken into account when assessing the reliability indicators, which leads to a decrease in their value, and, as a consequence, to an increase in the products cost. Objective. The purpose of the article is to improve the quantification accuracy of reliability values of electronic devices with variable structure by using a new model, which takes into account the operational time of individual subsets of elements of the object in its possible operational modes. Method. The paper analyzes the structures of radio electronic devices and their influence on reliability using methods of set theory, probability theory, discrete search theory and metrology. This allows objective quantification of reliability indicators values depending on the conditions of the product use: operating time for failure, average recovery time and the readiness coefficient. Results. An improved model of reliability of multiple mode objects with variable structure, which takes into account the features of structural design of the product, the features of its intended use (operating time in separate modes), and the influence of the quality of metrological support on the average recovery time has been obtained. This allows increasing the estimation of the real value of the complex indicator of reliability – readiness coefficient, and, as a consequence, reducing the value of the readiness coefficient. Conclusions. The use of the proposed model of quantitative estimation of the reliability indicators’ values of radio electronic devices with variable structure can reduce the cost of products while providing the required values of failure time and the average recovery time by reducing the requirements for the reliability of the base elements. The results obtained should be used in the design of perspective radio electronic devices to justify the choice of element of the minimum cost base while meeting the required requirements for the reliability of the product as a whole. x`x